Mental Comorbidity and Psychosocial Care in Patients with Cancer. - Dinkel, A.; Goerling, U.; Karger, A.; Teufel, M.; Zimmermann, T.; Stengel, A. (Deutsches Ärzteblatt International, 2025)
Background: Patients with cancer suffer from cancer- and treatment-specific, psychosocial and care-related stress and mental disturbances. Methods: This article is based on pertinent publications retrieved by a search in PubMed, as well as on the German clinical practice guideline on psycho-oncology. Results: The most common mental disorders in cancer patients are anxiety disorders, affective disorders, and adjustment disorders. The point prevalence of any mental disorder in patients with cancer is 20% to 50%. Common disease-associated psychological symptoms include distress (a non-specific experience of emotional discomfort), demoralization, and fear of cancer recurrence or progression. These can cause severe suffering even if they do not meet the diagnostic criteria for any particular mental disorder. Mental comorbidity is associated with complications of treatment, lesser adherence to treatment, lower quality of life, and increased mortality. Psychotherapeutic interventions are effective and show moderate to large effects in current meta-analyses with respect to the reduction of anxiety and depression and improvement in quality of life. These effects persist over several months of follow-up. The empirical evidence for psychopharmacotherapy in cancer patients is limited. Psychopharmacological treatment should be integrated into an overall psycho-oncological treatment plan. Conclusion: A large body of evidence shows that mental comorbidity is common among cancer patients and harmful to them. Psychotherapeutic interventions lessen the symptoms of mental disturbances and improve quality of life. Nonetheless, despite improvements in recent years, there are remaining barriers to the adequate provision of psychosocial care.